Quality of Life and Health Needs among Elderly aged 60-79 years in Paro, Bhutan - Gem Tshering; Karma Tenzin; Kamolnetr Okanurak; Junya Pattaraarchachai; Kanvee Viwatpanich (Bhutan Health Journal, 2023)
Introduction: The global population is undergoing a significant demographic shift, with a rapidly increasing number of elderly population. As people age, their health and quality of life become increasingly important considerations. The elderly population has unique health needs that must be addressed to ensure their well-being and maximize their quality of life. In Bhutan, elderly health needs are lacking despite information on health policy and planning. This study was proposed to assess quality of life and health needs among elderly aged between 60 – 79 years old under Naja, Dogar, Shaba, and Lyungni gewogs (blocks) under Paro district, Bhutan.